The Spatial Distribution of Bed Sediment on Fluvial System: A Mini Review of the Aceh Meandering River - Muhammad Irham (Graduate Program of Syiah Kuala University, 2016)
Dynamic interactions of hydrological and geomorphological processes in the fluvial system result in accumulated deposit on the bed because the capacity to carry sediment has been exceeded. The bed load of the Aceh fluvial system is primarily generated by mechanical weathering resulting in boulders, pebbles, and sand, which roll or bounce along the river bed forming temporary deposits as bars on the insides of meander bends, as a result of a loss of transport energy in the system. This dynamic controls the style and range of deposits in the Aceh River. This study focuses on the spatial distribution of bed-load transport of the Aceh River. Understanding the spatial distribution of deposits facilitates the reconstruction of the changes in controlling factors during accumulation of deposits. One of the methods can be done by sieve analysis of sediment, where the method illuminates the distribution of sediment changes associated with channel morphology under different flow regimes. Hence, the purpose of this mini review is to investigate how the sediment along the river meander spatially dispersed. The results demonstrate that channel deposits in the Aceh River are formed from four different type of materials: pebble deposited along upstream left bank; sand located on the upstream, downstream, and along meander belts; and silt and clay located along the cut bank of meander bends. Because of different depositional pattern, the distribution of the sediment along the river can be used as a surrogate to identify bank stability, as well as to predict critical geometry for meander bend initiation